Investigating the relationship between climate change, global warming and sustainable consumption / Wan Kalthom Yahya, Sharifah Zannierah Syed Marzuki - Yahya, Wan Kalthom; Syed Marzuki, Sharifah Zannierah (2012)
The purpose of this paper is to explore patterns of current consumption and production as well as to identify a better understanding the role of consumption that can reduces environmental deteriorations. Methods on how to change these consumption and production patterns to a better sustainable lifestyle are suggested. It is shown that global warming are becoming big impacts which it not only brings danger to human but also to other creature such as plant, animal and even the earth itself. This paper is very significant as global warming is prevalent with respect to consumption behaviour and sustainability. Looking into Malaysian context, the government has also taken several steps including setting.